Fruit Morphological Characteristics and β-carotene Content of Three Indonesian Dessert and Cooking Banana Cultivars - Ari Sunandar; Dedeh Kurniasih (Biosaintifika: Journal of Biology & Biology Education, 2019)
Approximately, 325 cultivars of bananas were found in Indonesia. They have variation in shape, taste, color of fruit pulp, essential vitamins and mineral. The β-carotene is one of essential nutrient in banana with various concentration in every cultivar. The aims of this research were to describe the morphological characteristics and to analyze β-carotene content of mature fruits of three different genomic groups of Indonesian dessert and cooking banana cultivars namely Berlin (AA/dessert), Barangan (AAA/dessert), and Kepok (ABB/cooking). Morphological characterizations of fruits were conducted according to Descriptor for Banana from International Plant Genetic Resources Institute. The β-carotene content of mature banana pulp was analyzed using High-performance liquid chromatography (HPLC) method with three replications. Banana fruit characters were analyzed based on 15 descriptors. The bananas were then subjected to clustering analysis. The result showed that β-carotene content were 27 μg 100g-1, 5 µg 100g-1, and 3 μg 100g-1 fresh weight respectively. Berlin showed the highest value of β-carotene. Cluster analyses formed two groups. The first group consists of Berlin and Barangan while the second one consists of Kepok. This study can be used as a a reference for people to consume bananas with high content of β-carotene in meeting the needs of vitamin A and as a consideration for the plant breeding especially for β-carotene improvement purpose.